The Imperative of Inclusive Education in Islam: An Analysis of the Rights of Children with Special Needs Through the Lens of Maqasid al-Shari'ah - Kurniawan, Erwin Hari; Fitria Rizki Rahmadani (VRISPRAAK : International Journal of Law, 2025)
Inclusive education represents the intersection of global human rights discourse and the imperative for social justice. However, its implementation within Muslim societies often requires a strong legitimation rooted in the Islamic theological and juridical tradition. This research aims to construct a juridical-philosophical argument regarding the right to education for children with special needs (CSN) by using the framework of Maq??id al-Shar?‘ah (the higher objectives of Islamic law) as its primary analytical tool. Through a qualitative method of hermeneutical library research, this article critically examines primary and secondary sources within the Islamic legal tradition. The analysis reveals that the educational rights of CSN are inherently supported by fundamental Islamic principles, such as universal human dignity (kar?mah ins?niyyah), justice (‘ad?lah), and the obligation to seek knowledge (?alab al-‘ilm). An analysis through Maq??id al-Shar?‘ah affirms that fulfilling this right is a direct manifestation of the effort to protect the five universal necessities (al-?ar?riyy?t al-khamsah): religion, life, intellect, lineage, and property. The findings have implications for the development of adaptive curricula, compassion-based (ra?mah) pedagogy, and proactive policies. It is concluded that Maq??id al-Shar?‘ah provides a dynamic and progressive ethical framework for advocating a truly inclusive and just educational system.